Our voices : psychology of women - Rider, Elizabeth A. 4 0 16; 5 (Belmont, CA : Wadsworth, 2000)
Explores the psychology of women of diverse backgrounds and discusses research findings about women's development and variations in patterns resulting from race, culture, social class, and sexual orientation.
Includes bibliographical references (p. [559]-591) and indexes.
Reference and Research Book News
Adult;Adult
Keywords: 2 -- 0; 6; Psychology.;Social conditions;Psychological aspects.;Psychological aspects.;Psychology.;Social conditions;Psychological aspects.;Psychological aspects. -- Women;Women;Sex role;Feminist psychology.;Women;Women;Sex role;Feminist psychology; 20; 2